2012
DOI: 10.1128/aem.02195-12
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Relative Risk of Cronobacter spp., Salmonella spp., and Listeria monocytogenes Associated with the Body Surfaces and Guts of Individual Filth Flies

Abstract: Although flies are important vectors of food-borne pathogens, there is little information to accurately assess the food-related health risk of the presence of individual flies, especially in urban areas. This study quantifies the prevalence and the relative risk of food-borne pathogens associated with the body surfaces and guts of individual wild flies. One hundred flies were collected from the dumpsters of 10 randomly selected urban restaurants. Flies were identified using taxonomic keys before being individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 67 publications
(87 reference statements)
1
51
0
Order By: Relevance
“…For example, in Japan, houseflies (Musca domestica L.) were implicated in transmission of Escherichia coli O157:H7 from reservoir animals to other animals and humans (44). Houseflies and blowflies collected from dumpsters of urban restaurants were shown to carry Cronobacter spp., Salmonella spp., and Listeria monocytogenes (45). Alam and Zurek (46) reported E. coli O157:H7 from the digestive tract of houseflies collected in a cattle feedlot from feed bunks and cattle feed storage, and they suggested that houseflies in cattle farms play a role in the dissemination of this food-borne pathogen.…”
Section: Antibiotic Resistance and Insectsmentioning
confidence: 99%
“…For example, in Japan, houseflies (Musca domestica L.) were implicated in transmission of Escherichia coli O157:H7 from reservoir animals to other animals and humans (44). Houseflies and blowflies collected from dumpsters of urban restaurants were shown to carry Cronobacter spp., Salmonella spp., and Listeria monocytogenes (45). Alam and Zurek (46) reported E. coli O157:H7 from the digestive tract of houseflies collected in a cattle feedlot from feed bunks and cattle feed storage, and they suggested that houseflies in cattle farms play a role in the dissemination of this food-borne pathogen.…”
Section: Antibiotic Resistance and Insectsmentioning
confidence: 99%
“…Cronobacter spp. are ubiquitous in nature and have been isolated from clinical, environmental, and food sources, most notably powdered infant formula and other dried foods (2,3), and, more recently, from surfaces and intestinal tracts of wild filth flies (4). The Cronobacter genus consists of seven species, C. condimenti, C. dublinensis, C. malonaticus, C. muytjensii, C. sakazakii, C. turicensis, and C. universalis (5,6).…”
mentioning
confidence: 99%
“…They move between feces and carcasses and food meant for human consumption. Bacteria acquired from filth can be transmitted to food, either via the fly exterior, e.g., body surface and mouth parts, or with feces and vomit that is produced during feeding (18)(19)(20)(21)(22)(23). In an experimental setting, flies were shown to transmit Campylobacter between chickens (24), and several studies have demonstrated similar pathogenic E. coli and Klebsiella strains on flies and in humans in hospital settings, as well as in small rural communities, suggesting their potential as transmission vehicles (25)(26)(27).…”
mentioning
confidence: 99%